Physical fitness performance, playing position and competitive level attained by elite junior soccer players: a 12-year study - Los Arcos, A.; Gonzalez-Artetxe, A. (Kinesiology, 2021)
The aim of this study was to look into the alleged impact of the physical fitness performance of elite junior soccer players on the professional career according to playing position. The physical tests (sprint test, countermovement jump [CMJ], and maximal aerobic speed [MAS]) performed by 165 players enrolled in the junior team of a Spanish 1st Division club (1998-2010) were evaluated. Players were classified as those who were promoted to the reserve team (Reserve Team) and those who were not (non-Reserve Team), and as those who were promoted to the Spanish 1st/2nd Divisions (PFL) and those who were not (NPFL) until the 2020-2021 season. Overall, no significant differences (p>.05) were found between the Reserve Team and non-Reserve Team or between the PFL and NPFL players in neuromuscular performance. Aerobic fitness was greater (p<.05; ES = .79 ± .60, moderate; mean difference = 3.0%) for the Reserve Team lateral midfielders in comparison to that for the non-Reserve Team. The results suggest that the impact of physical fitness on the promotion of elite junior soccer players is limited.